A methodology for empirical research and analysis in the field of cybersecurity - Ivanova, Yoana (Yearbook Telecommunications, 2022)
This article is considered to be a continuation of a publication by the author devoted to an algorithm for steganographic embedding of encrypted files in raster images (Yearbook Telecommunication, №9, 2022). The aim of this paper is proposing a methodology for empirical research and analysis on the field of cybersecurity which to contribute to various areas in cybersecurity. Its originality is expressed in the joint application of methods for research and analysis realized by various simulation environments for conducting experiments. This methodology has a specific structure as it is conditionally divided into two major parts depending on the type of the simulation process and software products used – a study of the direct impact of cyberattacks on communication networks by the method of the agent-based modelling and a study of potential steganography attacks using software for simulation of Artificial Neural Networks (ANNs) for the purposes of steganalysis.